Handbook of child and adolescent sexuality : developmental and forensic psychology - Bromberg, Daniel S.; O'Donohue, William T. (Oxford : Academic Press, 2013)
Adolescent and child sexuality is studied by developmental psychologists from a research perspective, and is of interest to forensic psychologists dealing with abuse and custody issues as well as rape cases. In many cases it is of interest whether the child in question was sexually active, to understand the extent to which an underage minor might have voluntarily participated in sexual activity as opposed to having been coerced. Previously researchers interested in the applications of their research needed to look to separate books, and forensic specialists needed to look to development books to find the information they may have needed. This handbook provides both audiences with the related information they need. It encompasses normative behavior and clinical disorders in one source. It applies the information on development and behavior to forensic issues.
Pt. 1. Ethical issues pertaining to the sexuality of minors -- pt. 2. Research strategies : how do we "know" what we "know"? -- pt. 3. Child and adolescent development -- pt. 4. Children and adolescents as sexual abuse victims -- pt. 5. Children with sexual behavior problems and adolescent sexual offenders.
Includes bibliographical references and index.
Keywords: Psychosexual disorders in children; Psychosexual disorders in adolescence; Sexually abused children; Sexually abused teenagers; Sexuality -- psychology; Adolescent; Child Abuse, Sexual; Child; Psychosexual Development